The Third Position. Issue 3 (13th November 2019) - Lees, Jan; Lomas, Fiona; Haigh, Rex
Abstract : Purpose: The purpose of this paper is to describe the role of the expert by experience, and its benefits and challenges. Design/methodology/approach: Review of the relevant literature and a case study has been performed. Findings: The role of the expert by experience is fluid and complex. Staff need to understand the ambiguities of the role. Practical implications: Experts by experience (XBXs) play an important role in TC practice. They need support and supervision. Staff need to learn about the complexities and fluidity of the role, and to be aware of its transitional position between service user and staff member. Social implications: XBXs challenge the binary notion of staff and service user. The role calls for a different relational rather than procedural conceptualisation. Originality/value: This is the first description of the lived experience of an expert by experience, working in a therapeutic community setting, with the analysis of the helpful and unhelpful aspects of the role.